THE EFFECT OF SUPPLY CHAIN MANAGEMENT (SCM) AND DECISION SUPPORT SYSTEM (DSS) WARSHIP SPARE PARTS ON OPERATION READINESS NAVAL FLEET COMMAND II - ramadhan, syaiful; kuncoro, anang dwi; soemantri, asep iwa (Ekspektra : Jurnal Bisnis dan Manajemen, 2021)
The importance of maritime defense and State Diplomacy is faced with the problems that exist in Koarmada II, especially related to the maintenance of warship, especially related to the support of On Board Spare (OBS) spare parts. Problem solving solutions are needed, among others, the first is to streamline and streamline the operation degree so that it is right on target against the reemergence of potential threats to maritime defense and security, the second is to evaluate, record, record and record everything related to spare parts needs OBS warship which carries out operational tasks, and improves the professionalism of soldiers based on technology and information, as well as increasing the ability to observe and supervise up to the ability to take action against perpetrators of violations of sovereignty at sea. The research approach used is descriptive quantitative method, which examines how Supply Chain Management (SCM) and Decision Support System (DSS) using the Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis approach which originates from questionnaires. Data analysis was assisted by SmartPLS 2.0 software. The research samples were soldiers who served in Koarmada II based in Surabaya. The results showed that Supply Chain Management had a significant effect on Operational Readiness. These results indicate that Supply Chain Management has a positive and significant direct effect on Operational Readiness. Decision Support System has a significant effect on Operational Readiness. These results indicate that the Decision Support System has a positive and significant direct effect on Koarmada II Operational Readiness. Supply Chain Management and Decision Support System for Warship Spare Parts do not have a positive and significant direct effect on Koarmada II Operation Readiness.